2017
DOI: 10.1016/j.renene.2016.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clear days from solar irradiance observations using a new method based on the wavelet transform

Abstract: A new method using the wavelet transform properties is developed to determine clear days of solar irradiance. These days are needed to model the solar radiation and to compare the existing empirical models. We use this method to process four years of global solar irradiation data collected at the Research Unit of Applied Renewable Energies at Ghardaïa city in Algeria. We also determine clear days from this data set using a standard method based on the clearness index criteria. The results show that the two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…where a ρ is the albedo of the cloudless sky, which can be computed with: We will apply this process to all global solar irradiance of clear days of the recorded data. The clear days are determined using the novel method developed by [37]. Each fit will give us a value of the aerosol single scattering albedo 0 w and a value of the forward scatterance c F .…”
Section: Single Scattering Albedo and Forward Scatteringmentioning
confidence: 99%
“…where a ρ is the albedo of the cloudless sky, which can be computed with: We will apply this process to all global solar irradiance of clear days of the recorded data. The clear days are determined using the novel method developed by [37]. Each fit will give us a value of the aerosol single scattering albedo 0 w and a value of the forward scatterance c F .…”
Section: Single Scattering Albedo and Forward Scatteringmentioning
confidence: 99%
“…ere is therefore no unique value or range of K t that can be universally designated to represent a clear sky. Djafer et al [45,46] noted that ranges of K t for clear sky may vary from one measurement site to another. As such, K t should be used in combination with other methods or parameters to identify clear sky days with better accuracy.…”
Section: Detection Of Clear Sky Daysmentioning
confidence: 99%
“…where, is the day the year. has often been adopted to indicate the relative clearness 𝑑 𝑛 𝑘 𝑡 of the atmosphere for sky categorization (Djafer et al, 2017;Escobedo et al, 2009;Kong and Kim, 2013;Wang et al, 2013) and it indicates the percentage of solar irradiance that radiates through the atmosphere. (Mellit et al, 2008) suggested that the choice of interval 𝑘 𝑡 values would also differ from one site to another.…”
Section: 𝑍 𝑠mentioning
confidence: 99%
“…No previous studies have presented analyses of each MI and its sky classification capability. (Li, 2010;Li et al, 2008), a precise selection of the models to estimate solar irradiance and for its prediction (Djafer et al, 2017;Ruiz-Arias and Gueymard, 2018), more accurate determination of the spectral components of solar radiation (Escobedo et al, 2009;Jacovides et al, 2007), and better prediction of photovoltaic production, to improve grid integration (Perveen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%